Creating Peace Across Borders: The East-West Path to Unity - Mitrayani, Dian; Peel, R. Don (Journal of International Students, 2018)
This article is based upon autobiographical narratives of two students exploring their experiences in finding commonality through an institutionalized domestic and international student community. Both students’ paths intersected at the East-West Center (EWC), an independent, public, nonprofit organization formed by the US Congress in 1960 with the goal of bringing people together through cooperative study, research, and dialogue. The co-authors describe various factors that facilitated cultivating inner peace and minimize imposed oppressive tendencies. In particular, they analyze the importance of a learning environment that motivates each student to deeply reexamine their relationship to cultural and disciplinary boundaries, through exposing them to multifaceted perspectives. Their conclusions highlight the importance of EWC as a place where bothdomestic and international students can build dialogue, debate, and learn from each other, across disciplinary sectors in a relaxed setting. EWC, with its unique diplomatic-building environment, is a learning prototype that has the potential to unify global diversity through developing unique partnerships of empowerment.